Freeze-thaw cycles as drivers of complex ribozyme assembly - Mutschler, Hannes (Nat Chem, 2015)
The emergence of an RNA catalyst capable of self-replication is considered a key transition in the origin of life. However, how such replicase ribozymes emerged from the pools of short RNA oligomers arising from prebiotic chemistry and non-enzymatic replication is unclear. Here we show that RNA polymerase ribozymes can assemble from simple catalytic networks of RNA oligomers no longer than 30 nucleotides. The entropically disfavoured assembly reaction is driven by iterative freeze-thaw cycles even in the absence of external activation chemistry. The steep temperature and concentration gradients of such cycles result in an RNA chaperone effect that enhances the otherwise only partially realized catalytic potential of the RNA oligomer pool by an order of magnitude. Our work outlines how cyclic physicochemical processes could have driven an expansion of RNA compositional and phenotypic complexity from simple oligomer pools.